Evaluation of future wind climate over the Eastern Mediterranean Sea - Gumuscu, Irem; Sahin, Cihan; Yuksel, Yalcin; Guner, H. Anil Ari; Islek, Fulya (ELSEVIER, 2024)
The aim of this study is to evaluate wind climate characteristics in the Eastern Mediterranean Sea until the end of the 21st century using the wind fields simulated by the EURO-CORDEX Regional Climate Models (RCM), namely the Rossby Centre regional atmospheric model (version RCA4). Long-term averages, long-term trends, and longterm variability in wind characteristics under two Representative Concentration Pathway (RCP 4.5 and 8.5) scenarios were assessed for two future periods: the near future for the years 2021-2060 and the middle future for the years 2061-2100. Relative to the historical period, the most remarkable changes in the mean wind speeds were projected under the RCP 8.5 scenario in the middle future in the central and southern Aegean Sea (exceeding 5 % increase) and in the eastern and northern Levantine basin (up to 5 % decrease), compatible with the definition of the climate scenarios as the RCP8.5 scenario assumes a rising radiative forcing until 2100. The changes in extreme wind characteristics are more noteworthy in agreement with the indicators of climate change (i.e., an increase in the intensity and the frequency of extreme events). 100-year return period wind speed increases by about 29 % in the western Levantine basin under the RCP 8.5 scenario while the most drastic decrease in 100-year extreme wind speed was found in the central Levantine basin with a reduction of exceeding -29 % for the middle future period under the RCP 8.5 scenario. These decreasing and increasing behaviors in extreme wind speeds are expected in the study area as the Mediterranean is affected by many climate systems.
Keywords: Eastern Mediterranean wind climate; Regional climate models; Projected changes; Future trends; Climate change; WAVE CLIMATE; CHANGE PROJECTIONS; TEMPERATURE; MODEL; CIRCULATION; SCENARIOS; EXTREMES; IMPACTS; EUROPE; TRENDS; Environmental Sciences & Ecology; Marine & Freshwater Biology